Modified Method for Chemical Extraction of Palynomorphs from Petroleum Source Rocks - Al-Shukry, Abbas H; Al-Dahhan, Wedad H (Al-Nahrain Journal of Science, 2012)
Palynomorphs were efficiently separated from paleogene rock samples using HCl/HF mineral acids to digest carbonaceous silicates of inorganic sedimentary rocks matrix to extract the palynomorphs individually using cellosize solution, then fixed upon microscope glass slides for visual optical test .The traditional procedure was developed by the control of acid concentrations, residence time as well as the use of ultra sonic bath to obtain well structured structures useful for visual optical tests. The data of analytical chemical analysis (TOC%, S2, HI and vitrinite scale) for source rocks confirm the accuracy of the modified procedure to predict H.C. product of the well whether its oil or oil/gas prone .